Increasing BMEP for downsizing of internal combustion engines through an advanced turbocharging concept - Amy, Paris, author; Olsen, Daniel, advisor; Kirkpatrick, Allan, committee member; Johnson, Jerry, committee member (Colorado State University. Libraries, 2012)
In order to meet more strict national emissions and fuel economy regulations automotive manufacturers are turning to downsized boosted engines. A SuperTurbo™ is a device that delivers the high speed torque of a turbocharger and the low speed torque of a supercharger, with the benefits of turbo-compounding. This technological advantage makes it a perfect candidate for engine downsizing and boosting application. In order to validate the SuperTurbo™ as viable technology for engine downsizing, a General Motors Ecotec LSJ 2.0l I4 engine was modeled using the industry standard engine simulation software GT-Power. Two additional models of a SuperTurbocharged Ecotec LSJ engine were also generated. One SuperTurbocharged Ecotec engine was tuned to match the performance map of the stock Ecotec LSJ engine and another SuperTurbocharged Ecotec engine was tuned to match the performance map of a larger General Motors Vortec LMG 5.3l V8. Simulation results from the stock Ecotec model were compared to both of the results from the SuperTurbocharged models in order to validate reported efficiency gains through SuperTurbo™ use. Additionally, the models were compared to determine how feasible a SuperTurbo™ is for engine downsizing while maintaining power output. The simulation results showed improvements in engine brake specific fuel consumption (BSFC) up to 26% at high engine speeds when compared to the GM Vortec LMG engine and BSFC improvements up to 21% at 4500 rpm when compared to the stock Ecotec LSJ engine. At lower to mid-engine speeds both models saw BSFC improvements between 5 and 20%. It was concluded that downsizing an engine with a SuperTurbo™ was a practical way to improve engine BSFC while maintaining performance.
Keywords: BMEP; turbocharging; engine; downsizing